2017
DOI: 10.1080/14767058.2017.1342796
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vitamin D deficiency in pregnant mothers in Tehran and investigating its association with serum glucose and insulin

Abstract: Vitamin D deficiency/insufficiency is prevalent among pregnant women. Factors causing this epidemic need investigation. Promoting consumption of vitamin D-fortified foods and supplements among pregnant women is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…Consistent predictors of low 25(OH)D levels across the lifecycle included increasing age, female gender, high weight or body mass index (BMI), low physical activity, low intake of calcium or vitamin D supplements, concealed clothing, low sun exposure duration, winter season, lower education or socio-economic status, and urban residence ( Hoteit et al, 2014 ; Al-Mahroos et al, 2013 ; Khalesi et al, 2012 ; Khuri-Bulos et al, 2013 ; Fouda et al, 2017 ; Mohamed and Al-Shehri, 2013 ; Djennane et al, 2014 ; Shady et al, 2015 ; Ebrahimi et al, 2014 ; Kelishadi et al, 2014 ; Nikooyeh et al, 2017 ; Nichols et al, 2012 ; Al-Daghri et al, 2015 ; Al-Daghri et al, 2016 ; Al Shaikh et al, 2016 ; Kaddam et al, 2017 ; Sulimani et al, 2016 ; Korchia et al, 2013 ; Bezrati et al, 2016 ; Narchi et al, 2015 ; Rajah et al, 2012 ; Al-Sahlawi et al, 2014 ; Botros et al, 2015 ; Khalessi et al, 2015 ; Naseh et al, 2017 ; Al-Ajlan et al, 2015 ; Golbahar et al, 2013 ; Ardeshir Larijani et al, 2014 ; Esteghamati et al, 2014 ; Jaddou et al, 2012 ; Alfawaz et al, 2014 ; Ardawi et al, 2012 ; Tuffaha et al, 2015 ; Zhang et al, 2016 ; El Maghraoui et al, 2012 ; Saliba et al, 2012a ; El-Menyar et al, 2012 ; Sayed-Hassan et al, 2014 ; Sridhar et al, 2016 ; Hosseini et al, 2014 ; Saliba et al, 2012b ). Added to that is smoking status in adults and maternal weight at delivery ( Appendix II ) ( Hoteit et al, 2014 ).…”
Section: Prevalence Of Low 25(oh)d Concentrations By Age Category Andmentioning
confidence: 99%
“…Consistent predictors of low 25(OH)D levels across the lifecycle included increasing age, female gender, high weight or body mass index (BMI), low physical activity, low intake of calcium or vitamin D supplements, concealed clothing, low sun exposure duration, winter season, lower education or socio-economic status, and urban residence ( Hoteit et al, 2014 ; Al-Mahroos et al, 2013 ; Khalesi et al, 2012 ; Khuri-Bulos et al, 2013 ; Fouda et al, 2017 ; Mohamed and Al-Shehri, 2013 ; Djennane et al, 2014 ; Shady et al, 2015 ; Ebrahimi et al, 2014 ; Kelishadi et al, 2014 ; Nikooyeh et al, 2017 ; Nichols et al, 2012 ; Al-Daghri et al, 2015 ; Al-Daghri et al, 2016 ; Al Shaikh et al, 2016 ; Kaddam et al, 2017 ; Sulimani et al, 2016 ; Korchia et al, 2013 ; Bezrati et al, 2016 ; Narchi et al, 2015 ; Rajah et al, 2012 ; Al-Sahlawi et al, 2014 ; Botros et al, 2015 ; Khalessi et al, 2015 ; Naseh et al, 2017 ; Al-Ajlan et al, 2015 ; Golbahar et al, 2013 ; Ardeshir Larijani et al, 2014 ; Esteghamati et al, 2014 ; Jaddou et al, 2012 ; Alfawaz et al, 2014 ; Ardawi et al, 2012 ; Tuffaha et al, 2015 ; Zhang et al, 2016 ; El Maghraoui et al, 2012 ; Saliba et al, 2012a ; El-Menyar et al, 2012 ; Sayed-Hassan et al, 2014 ; Sridhar et al, 2016 ; Hosseini et al, 2014 ; Saliba et al, 2012b ). Added to that is smoking status in adults and maternal weight at delivery ( Appendix II ) ( Hoteit et al, 2014 ).…”
Section: Prevalence Of Low 25(oh)d Concentrations By Age Category Andmentioning
confidence: 99%
“…Moreover, Karras et al [35] out of literature systemic review found the prevalence of VD insufficiency among pregnant Greece women ranged from 9.3 to 41.4%, whereas that of VD deficiency from 22.7 to 90.3%. Furthermore, Naseh et al [36] and Kilicaslan et al [37] detected VD deficiency rates of 27% and 53% and insufficiency rates of 73% and 47%, respectively, in their series of pregnant women. Moreover, Wierzejska et al [38] detected higher VD levels in maternal and umbilical cord blood in summer than in winter, but only 16% of studied pregnant women had the optimal VD level during summer.…”
Section: Discussionmentioning
confidence: 92%
“…In line with these data, Karras et al 12 detected a prevalence of VD insufficiency and deficiency among pregnant women in Mediterranean region in ranges of 9.3-41.4% and 22.7-90.3%, respectively. Thereafter, Naseh et al 11 reported VD deficiency in 27% and insufficiency in 73% of their sample of Iranian pregnant women. Moreover, Chakhtoura et al 26 found the prevalence of HVD, defined as a 25-hydroxyvitamin D level <50 nmol/L, ranged between 44 and 96% in adults and 54-90% in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…VD-ST was found to specific significant (p=0.010) predictor for decreased incidence of PAM with AUC=0.595. In line with the beneficial effect of VD-ST on pregnancy outcome, Naseh et al 11 suggested promoting consumption of VD-fortified foods and supplements among pregnant women to improve maternal and neonatal outcomes. Also, Krieger et al 37 suggested that VD-ST during pregnancy should receive more attention in clinical practice as it was the most actionable determinant of VD status at the 3 rd trimester and in neonatal cord blood and Wheeler et al 38 recommended 1 st trimester maternal VD screening and targeted supplementation for those "at risk".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation